(untitled) (International Journal of Engineering and Computer Science, 2025)
This article presents an algorithmic solution for calculating the heating efficiency of an industrial facility when water cooling is used as the setup for mining farm equipment. Crypto mining belongs to industries that are actively developing, and a high volume of electricity consumption is generated. Efficient usage of wasted heat is a key factor in energy efficiency improvement, and also contributes to sustainability within energy systems. In this paper, this study occupies a vital place, as an increase in the more efficient exploitation of thermal resources leads not only to reduced consumption but also to reduced carbon emissions. That means dual targets-environmental and economic are achieved. The novelty lies in collecting and applying an integrated methodology for assessing the effectiveness of heating systems while addressing water cooling for mining equipment. It will use the three approaches: energy balance, exergy analysis, and CFD technology simulation, together with a short review of regulatory requirements such as ASHRAE and Energy Reuse Factor, to give an appropriate thermal potential assessment and loss source identification, hence optimization of design and operation for heating systems based on mining farms. The main conclusions are that a simple energy balance is sufficient for small-scale facilities. At the same time, more complex methods, such as exergy analysis and CFD simulation, are required for large data centers and industrial sites with higher loads. System efficiency improves drastically with the application of heat pumps, along with a reduction in hydraulic and pump equipment losses. The economic benefits of heat utilization from mining farms will be able to compete with traditional heat sources, such as gas boilers. This will be of interest to engineers, designers, and researchers working on energy efficiency. This will attract investors interested in sustainable yet economically viable solutions that can be used for heating industrial facilities.